Kinetics and Thermodynamics of Hydrogen Oxidation and Oxygen Reduction in Hydrophobic Room-Temperature Ionic Liquids - Rollins, Julie B. (2009)
In this study 1-dodecyl-3-methylimidazolium (C(12)mim) bis(pentafluoroethylsulfonyl)imide (BETI) and 1-dodecylimidazolium (C(12)im) BETI hydrophobic room-temperature ionic liquids (RTILs) were synthesized and used as proton-conducting electrolytes in a nonhumidified feed gas electrochemical cell. The ionic conductivities of C(12)mimBETI and C(12)imBETI were similar and increased linearly with an increase in temperature from 20 to 130°C. However, when used in the electrochemical system the protic water-equilibrated C(12)imBETI had a larger maximum current and power density compared to the aprotic water-equilibrated C(12)mimBETI. The effect of water content on the reaction rates and thermodynamics of these hydrophobic RTILs was also examined. The efficiency of the C(12)mimBETI increased upon removal of water while that of the C(12)imBETI decreased in efficiency when water was removed. The water structure in these RTILs was examined using attenuated total internal reflection Fourier transform IR spectroscopy and depended on the chemical structure of the cation. These studies give further insight into the possible mechanism of proton transport in these RTIL systems.